Radikalisme Agama Dalam Perspektif Pendidikan - Hujair AH Sanaky; Edy Safitri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2015)
Indonesia is a pluralistic society, it is necessary that education should provide an overview and moral ideals of religion contextually. In the educational process required a review of the religious doctrines, like the doctrine of jihad. That is, jihad is no longer understood as an endorsement of Islam to violence in spreading faith. The plurality of religion and belief is no longer understood as a potential riot, but be a potential to be invited to jointly implement the teachings for the sake of humanity. All religions should claim peace and human safety. In this context, education has an important role to foster self-scratch, so not only can receive others, but also able to work with different beliefs or religion. This means that education should enable the growth of the brotherhood in unity, so as to jointly build a new world that is more meaningful for all of humanity. So that, design education should accommodate pluralist and tolerant. Attitude required teachers of religion that is tolerant and pluralist.